Development Of Edible Oleogel For Capsaicin Delivery - Wong, Kean Seng (Universiti Sains Malaysia, 2020)
Capsaicin is a lipid bioactive compound that can enhance the lipid metabolism in human body. However, capsaicin is pungent when consume and as lipid bioactive component it can be easily oxidized during storage. Oleogelation is a novel technique that entrap liquid oil by using oleogelator. The study was aim to develop oleogel using wax to deliver capsaicin. The effects of wax concentrations (2 %, 4 % and 6 % w/w) and crystallization temperatures (5 °C, 15 °C and 25 °C) on the physical and thermal properties, crystallization properties, oxidative stability, and capsaicin entrapment of the capsaicin oleogel were studied using response surface methodology (RSM). The hardness, thermal properties (crystallization and melting points) and secondary oxidation (anisidine value, AV) of the oleogel were significantly increased with the increase in wax concentration with quadratic effects except hardness showing linear effects but were not significantly influenced by crystallization temperature. Based on the result, it could be stated that concentration of wax had significantly influenced on most of the physical properties, whereas Tset were not greatly influence in most of the physical properties. In oxidative stability, it had been found that candelilla oleogel with 6 % wax and Tset of 25 °C had better oxidative stability where PV was 2.37±0.03 mmol/kg and p-AV was 3.69±0.27 compared to control. This was due to structure of oleogel that act as the protective barrier against oxidation. Last but not least, it was found that capsaicin content for candelilla oleogel with 2% had relatively higher than the others. However, the linkage did not determine between both variables and capsaicin content.